2004
DOI: 10.1213/01.ane.0000134685.75813.eb
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Argatroban on Thrombin Generation and Hemostatic Activation In Vitro

Abstract: We evaluated argatroban, a direct thrombin inhibitor, as a heparin adjunct for anticoagulation. Platelet-poor plasma (PPP) was isolated from blood collected from 12 volunteers. Thrombin generation measurements were performed in donor PPP that was mixed with antithrombin (AT)-poor plasma to yield AT levels of 0%, 20%, 60%, and 100%. Effects of argatroban (0-1.0 microg/mL), heparin (0.25 U/mL), or the combination of argatroban (0.5 microg/mL) and heparin were also studied. The addition of increasing concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 24 publications
3
19
0
1
Order By: Relevance
“…Results from the current study showed that the anticoagulant response was decreased over multiple various AT levels, which is in agreement with two other studies (Tanaka et al, 2004(Tanaka et al, , 2005. The anticoagulant response was limited to <40% of maximum until AT levels were above 0AE5 U/ml.…”
Section: S Kuhle Et Al ª 2006supporting
confidence: 93%
“…Results from the current study showed that the anticoagulant response was decreased over multiple various AT levels, which is in agreement with two other studies (Tanaka et al, 2004(Tanaka et al, , 2005. The anticoagulant response was limited to <40% of maximum until AT levels were above 0AE5 U/ml.…”
Section: S Kuhle Et Al ª 2006supporting
confidence: 93%
“…It is conceivable that systemic extension of thrombus formation might have been prevented by bivalirudin-mediated thrombin inhibition. A potential use of direct thrombin inhibitors in cases of intravascular thromboses in AT deficiency is yet to be evaluated [22,70,71].…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of antithrombin, the CLT was normalized even in the presence of factor VIII deficiency (Table 1). It was speculated that thrombin is capable of extensive substrate cleavage including TAFI in the absence of antithrombin [10,20]. Indeed, an increased peak thrombin level in AT(À)/FVIII(À) plasma underlies increased thrombin substrate (Z-GGR-AMC) cleavage, although the lag time was not affected by antithrombin depletion (Table 2 and Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of a coagulation factor deficiency on thrombin generation manifests as a prolonged lag time and/or a decrease in the peak height of thrombin generation as calculated from the amount of substrate cleavage. The decrease in anticoagulant (antithrombin) has an opposite effect because thrombin becomes less inhibited by antithrombin, cleaving more substrate [10,11]. To measure the peak level of endogenous thrombin generation, 80 ml normal or factor-deficient plasma was added to microtiter plate wells, followed by the addition of 20 ml diluted Actin FS (1 : 20 dilution; Dade Behring, Marburg, Germany).…”
Section: Endogenous Thrombin Generation Assaymentioning
confidence: 99%